Carding nomination criteria for the Sport Canada athlete assistance program (Canadian Snowboard Federation, 2006)
The Athlete Assistance Program (AAP) is a program of direct funding from the Government of Canada to selected athletes in Olympic sports, and is administered by Sport Canada. Athletes are selected for nomination to the program based on criteria developed by the CSF and approved by Sport Canada. Athletes are recognized for funding (they are "Carded") at different levels of support, depending on their competition results. The purpose of the Athlete Assistance Program is to provide a degree of financial support to top-ranked Canadian athletes to assist them with the living and training expenses they must incur in order to excel at the international level. This document sets out the criteria used to nominate CSF High Performance Program athletes for Carding. These criteria have been developed within the context of the Sport Canada Athlete Assistance Program Policy and Procedures document, which also contains additional information concerning the Athlete Assistance Program. In the event of circumstances not otherwise covered in these documents, a decision on Carding will be reached through discussions between CSF and Sport Canada.